Fragmentation of Authority in National Cyber Defense A Legal Analysis of Overlapping Inter-Agency Authority and the Urgency of Integrated Command - Restu Putri Pamungkas; Bambang Kustiawan; Asep Adang Supriyadi; Guntur Eko Saputro (PALAR | PAKUAN LAW REVIEW, 2026)
The evolution of cyberspace as the fifth domain of warfare has transformed the national defense landscape, where hybrid threats can now disrupt sovereignty without physical war declarations. Indonesia responds to this challenge through the Total People's Defense and Security System (Sishankamrata) doctrine, yet its implementation is hindered by acute institutional fragmentation. This study aims to analyze the implications of regulatory disharmony on strategic defense effectiveness and formulate an ideal legal construction for national cyber governance. Using normative legal research methods with statutory and conceptual approaches, this study finds that current sectoral regulations create legal antinomy between defense mandates (Military/TNI), law enforcement (Police/Polri), and administrative security (National Cyber and Crypto Agency/BSSN). An asymmetry of authority is identified where BSSN, as the coordinator, is based only on a Presidential Regulation, lacking operational coercive power over institutions established by Law. The absence of legal escalation mechanisms in the "grey zone" leads to decision-making paralysis during crises. This study concludes the need for legal reconstruction through the enactment of a Cyber Security and Defense Law as lex specialis. This law must institutionalize a Unified Command System that establishes a single authority and clear thresholds for transferring operational control from civil to military domains, ensuring a rapid, integrated, and legally certain state response. Keywords: National Cyber Security Policy, Strategic Defense, Authority Fragmentation, Unified Command, Total Defense System.